Strategi Copywriter dalam Pembuatan Naskah Iklan Komersial Produk Ronas di PT Revass Utama Medika - Sekilawati, Suci Rahma; Sartik, Ika (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the copywriter’s strategy in creating commercial advertisement scripts for Ronas products at PT Revass Utama Medika. The method employed is a case study with data collection through interviews, observation, and literature review. Findings indicate that the application of the AISAS model (Attention, Interest, Search, Action, Share) is effective in developing scripts that attract attention, build interest, and encourage consumer purchasing actions. The creative process follows Wallas’ stages of creative thinking, which aids in producing persuasive and communicative scripts. In conclusion, a structured copywriting strategy can enhance the effectiveness of commercial advertisements in achieving skincare product marketing goals. This study recommends further development of more adaptive and interactive digital marketing communication strategies.